Study of the control of urban filariasis by the case detection method through night blood filming and treatment programme. - Ratnapriya, W.M.S (My University, 1987)
While the NBF programme is being carried out at a satisfactory level,the following measures are recommended to imperove the final outcome of the programme: The actual population at present in an area should be reassessed and strictly allocated among F.AA in the range of 10,000-15,000 with additional F.AA being posted to this order to cover up the addtional population if this is not possible,a detailed study should be undertaken in regard to the minimum number of blood films to be done per month and this figure increased together with additional incentives.Eductional qualifications necessary for the recruitment of F.AA be raised to advanced level and this criteria strictly adhered to.A proper course of health education together with a course in spoken english and tamil be made part of the training of F.AA and only those who qualify in the language course be appointed to areas where the percentage of those speaking above two language is high.